2020
DOI: 10.1136/bjophthalmol-2019-315052
|View full text |Cite
|
Sign up to set email alerts
|

Progression from ocular hypertension to visual field loss in the English hospital eye service

Abstract: BackgroundThere are more than one million National Health Service visits in England and Wales each year for patients with glaucoma or ocular hypertension (OHT). With the ageing population and an increase in optometric testing, the economic burden of glaucoma-related visits is predicted to increase. We examined the conversion rates of OHT to primary open-angle glaucoma (POAG) in England and assessed factors associated with risk of conversion.MethodsElectronic medical records of 45 309 patients from five regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…VF data were extracted from an EMR (Medisoft; Medisoft Ltd., Leeds, UK) from five regionally different National Health Service Hospital Trust glaucoma clinics in England in November 2015 as described elsewhere. 18 20 In short, all patient data were anonymized at the point of data extraction and subsequently transferred to a single secure database held at City, University of London. Subsequent analyses of the data were approved by a research ethics committee of City, University of London.…”
Section: Methodsmentioning
confidence: 99%
“…VF data were extracted from an EMR (Medisoft; Medisoft Ltd., Leeds, UK) from five regionally different National Health Service Hospital Trust glaucoma clinics in England in November 2015 as described elsewhere. 18 20 In short, all patient data were anonymized at the point of data extraction and subsequently transferred to a single secure database held at City, University of London. Subsequent analyses of the data were approved by a research ethics committee of City, University of London.…”
Section: Methodsmentioning
confidence: 99%
“…Refinements of this tool could be able to identify patients suitable for less intense monitoring; data from the English HES service indicate that less than 20% of OHT patients convert to POAG over a 5year period, suggesting some groups may require less intensive follow-up. 41 Future sub-group refinements of such tools could also prove useful and further allow the adjustment of HES resources depending on disease characteristics (e.g. OHT, angle closure, secondary glaucoma).…”
Section: Discussionmentioning
confidence: 99%
“…There was an association between the baseline stratification and the proportion of patients requiring an increased number of treatment escalations to maintain the eye-specific target IOP. In total, 9.9% (41) of eyes stratified as Green, 17.8% (34) of eyes stratified as Amber and 22.4% (24) of eyes stratified as Red needed treatment escalations that fell outside the IQR range (0 to 2) of the LiGHT cohort treatment escalations during the course of the 3-year trial (χ 2 (2, N=713)=14.6, p=0.001) (Figure 3).…”
Section: Disease Managementmentioning
confidence: 99%
“…EMGT study also revealed that a reduction by 1 mmHg in IOP from baseline leads to 10% decrease in the risk of glaucoma progression, whereby 1 mmHg increment leads to 11% increase in the risk of glaucoma progression [8]. IOP lowering therapy reduces the conversion rate from OHT to POAG with a predicted 5-year conversion rate of 14% and 26.9% in the treated and untreated group, respectively [15]. Despite the strong association between OHT and glaucoma, there is a subset of POAG patients that has glaucomatous neuropathy in the absence of ocular hypertension known as 'normaltension glaucoma'.…”
Section: Ocular Hypertensionmentioning
confidence: 94%
“…Although not all patients with increased IOP develop POAG, it has been recognized as the most important risk factor for the disease and control of IOP remains the main focus of treatment in POAG. Patients without glaucomatous signs and symptoms but having IOP above 21 mmHg are diagnosed to have ocular hypertension (OHT) and ocular hypertensive patients have a 17.5% cumulative risk of conversion to glaucoma in 5-year [15]. The findings of the studies such as OHTS and EMGT suggested that elevated IOP is a significant predictive factor for the development and progression of POAG [6]- [8].…”
Section: Ocular Hypertensionmentioning
confidence: 99%